Fostering Mathematical Creative Thinking Through the DOCAR Instructional Model: An Embedded Mixed-Methods Investigation Across Mathematical Self-Efficacy Levels - Shoffan Shoffa; Febriana Kristanti; Alfina Damayanti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2026)
This study examined the effectiveness of the DOCAR instructional model in enhancing mathematical creative thinking, differences across mathematical self-efficacy levels, and students' learning processes during instruction. An embedded concurrent mixed-methods design was employed with quantitative data as the primary component. Sixty seventh-grade students from a junior secondary school in Surabaya, Indonesia, participated in a nonequivalent control group quasi-experiment. Mathematical creative thinking and self-efficacy were measured using validated instruments. Quantitative data were analyzed using Two-Way ANOVA and Tukey's HSD test, while qualitative data from classroom observations, students' written responses, and interviews were analyzed thematically. Students receiving the DOCAR instructional model achieved significantly higher mathematical creative thinking than those receiving conventional instruction, F(1, 54) = 160.83, p < .001, partial η² = .749. Mathematical self-efficacy also had a significant effect, F(2, 54) = 342.38, p < .001, partial η² = .927, whereas the interaction effect was not significant, F(2, 54) = 0.29, p = .747. Qualitative findings showed that collaborative discussion, reflection, and problem solving promoted mathematical reasoning and confidence. The DOCAR instructional model effectively fosters mathematical creative thinking across different levels of mathematical self-efficacy.